Порівняльний аналіз податкових доходів бюджетів окремих країн ЄС та державного бюджету України - Сочка Катерина; Sochka Kateryna; Szocska Katalin (ДВНЗ «УжНУ», 2023)
Резюме. У статті вивчено теоретичні підходи українських та зарубіжних науковців щодо взаємозв’язку рівня економічного розвитку країни та централізації частини ВВП через податкові інструменти, досліджено фіскальну ефективність прямого та непрямого оподаткування, його вплив на економічні процеси, а також окреслено окремі переваги та недоліки прямих та непрямих податків з точки зору реалізації пріоритетів соціально-економічної політики держави. Вивчено динаміку частки податкових доходів бюджетів окремих країн ЄС (Польща, Угорщина, Румунія) та державного бюджету України у ВВП за 2010 – 2020 роки. Здійснено порівняльний аналіз структури податкових доходів бюджетів окремих країн ЄС (Польща, Угорщина, Румунія) та державного бюджету України у розрізі прямих (податки на доходи та прибуток) та непрямих податків (податки на товари та послуги). Окреслено окремі напрямки вдосконалення прямого оподаткування в напрямку поступового посилення його значення.

Abstract. An essential task for governments in present time is to elaborate financially sustainable system of budget revenue generation, which ensures reliable accumulation of resources in the long term. The absolute majority of budget revenues are accumulated through taxes, which represent a compulsory and unrequited payments by citizens and businesses on the benefit of state institutions. In financial, economic and political instability, the discussion of scientists regarding the priority of further expansion of the tax base of certain payments and the creation of an economically justified and fiscally effective balance between direct and indirect taxation is extremely relevant. Purpose. Is to carry out a comparative analysis of the structure of tax revenues of the state budget of Ukraine and the budgets of neighboring EU countries in terms of direct and indirect taxation. This research examines the budget indicators of such post-socialist countries as Poland, Hungary and Romania. Results. The fiscal efficiency of direct and indirect taxation, its impact on economic processes as well as the selected advantages and disadvantages of direct and indirect taxes regarding the priorities of state policy are analyzed. The dynamics of the share of budget tax revenues in GDP for selected EU countries (Poland, Hungary, Romania) and Ukraine during 2010-2020 were studied. A comparative analysis of the structure of tax revenues of the budgets for selected EU countries (Poland, Hungary, Romania) and Ukraine was carried out in the terms of direct (income and profit taxes) and indirect taxes (taxes on goods and services). Conclusions. Some suggestions for improving direct taxation with the purpose to increase its importance in Ukraine are outlined, in particular, the use of a progressive scale of taxation of people’s incomes and business profits, the introduction of a tax on withdrawn capital, taxation of luxury items and luxury services.
Comparative analysis of tax revenues of budgets of selected EU countries and the state budget of Ukraine
Редакційна колегія: http://visnyk-ekon.uzhnu.edu.ua/about/editorialTeam Зміст: http://visnyk-ekon.uzhnu.edu.ua/issue/view/16646
Keywords: бюджет; податкові надходження; пряме оподаткування; непряме оподаткування; фіскальна ефективність; економічний розвиток; budget; tax revenues; direct taxation; indirect taxation; fiscal efficiency; economic development